2011
DOI: 10.1107/s1600536811003849
|View full text |Cite
|
Sign up to set email alerts
|

Redetermination of 3-methylbenzoic acid

Abstract: The asymmetric unit of the title compound, C8H8O2, contains two crystallographically independent mol­ecules, which form dimers linked by O⋯H—O hydrogen bonds. The benzene rings in the dimers are inclined at a dihedral angle of 7.30 (8)° and both methyl groups display rotational disorder. This redetermination results in a crystal structure with significantly higher precision than the original determination [Ellas & García-Blanco (1963 ▶). Acta Cryst. 16, 434], in which the authors reported only the unit-cell pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In addition, methylbenzoic acid is used as an intermediate for polymer stabilizers, pesticides, and light sensitive compounds. The crystal structure of 3-methylbenzoic acid (3MBA) [34] has been reported. In this research paper, preparation, structural and characterization of cocrystal compound were reported by using PXRD, FTIR, 1 H NMR and 13 C NMR spectroscopes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, methylbenzoic acid is used as an intermediate for polymer stabilizers, pesticides, and light sensitive compounds. The crystal structure of 3-methylbenzoic acid (3MBA) [34] has been reported. In this research paper, preparation, structural and characterization of cocrystal compound were reported by using PXRD, FTIR, 1 H NMR and 13 C NMR spectroscopes.…”
Section: Introductionmentioning
confidence: 99%